External Locus of Control dan Perilaku Konsumtif terhadap Penggunaan Shopee Paylater “Beli Sekarang Bayar Nanti” - Dewi Kusuma Wardani; Indra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the external locus of control and consumptive behavior towards the use of shopee pay later "buy now pay later". Students studying in the Special Region of Yogyakarta became the sample population in this study. The method used in this study used quantitative methods by distributing questionnaires to 104 respondents, while for data collection using the snowball sampling method. This study concluded that external locus of control and consumptive behavior positively influenced the use of shopee pay later "buy now pay later".